(untitled) (مجلة إحالات, 2026)
Literature is an honest expression of the experiences that a person experiences in various aspects of life, and Islamic literature is an effective contributor to drawing a vivid picture of human reality. It is used to indicate literature whose starting point is from the Islamic perception of life. In this research paper, we will try to monitor the poetic and aesthetic aspects in some of the poems of a poet. Asceticism and Wisdom “Abu Al-Atahiyya” This can only be achieved by analyzing the internal structures of the poetic text through the stylistic approach, as it is the most capable of methods to monitor the aesthetic phenomena in the poem. Perhaps the question raised here is: What are the aesthetic dimensions and poetic features in the Islamic poetic text? Has Islamic literature enriched the treasury of Arabic literature? We will try to answer these two questions through the levels of the stylistic approach that enable us to explore the depths of the text and highlight its aesthetic features, beginning by giving a brief overview of it and then moving to the applied aspect.